2022
DOI: 10.3389/fonc.2022.939877
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open liver resection for hepatocellular carcinoma in elderly patients: A systematic review and meta-analysis of propensity score-matched studies

Abstract: PurposeLaparoscopic liver resection (LLR) is a widely practiced therapeutic method and holds several advantages over open liver resection (OLR) including less postoperative pain, lower morbidity, and faster recovery. However, the effect of LLR for the treatment of hepatocellular carcinoma (HCC) in elderly patients remains controversial. Therefore, we aimed to perform the first meta-analysis of propensity score-matched (PSM) studies to compare the short- and long-term outcomes of LLR versus OLR for elderly pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…Our analysis indicated that there was no significant difference in long-term survival between the two surgical approaches. These findings align with those of previous studies ( 9 - 11 ). However, it is important to note that further research is necessary to provide more detailed survival data and adjusted HR as time-to-event data, which can enhance the precision and depth of our understanding in this context.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our analysis indicated that there was no significant difference in long-term survival between the two surgical approaches. These findings align with those of previous studies ( 9 - 11 ). However, it is important to note that further research is necessary to provide more detailed survival data and adjusted HR as time-to-event data, which can enhance the precision and depth of our understanding in this context.…”
Section: Discussionsupporting
confidence: 93%
“…We excluded studies with mixed populations, encompassing patients under 65 years of age or those with other liver malignancies like intrahepatic cholangiocarcinoma, liver metastases, or recurrent liver cancer. Previously, Jiang et al ( 10 ) conducted a review and meta-analysis encompassing 14 studies comparing laparoscopic hepatectomy to open hepatectomy, while Wang et al ( 9 ) performed meta-analyses using 12 propensity score-matched studies. Brolese et al ( 11 ) reviewed eight studies comparing minimally invasive LRs (laparoscopic or robotic) to OLR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of whether minimally invasive liver surgery (MILS) improves post-resection outcomes for HCC is a topic that has garnered considerable attention in the literature. Numerous studies provide substantial evidence supporting the significant advantages of MILS in enhancing short-term surgical outcomes for patients undergoing HCC resection when compared to the traditional open technique, particularly in high-volume centers [ 40 , 41 , 42 , 43 , 44 , 45 ]. Both laparoscopic and robotic techniques have demonstrated their efficacy in reducing the risk of post-hepatectomy liver failure and mitigating postoperative complications [ 46 , 47 ].…”
Section: Does Mils Improve Post-resection Outcomes?mentioning
confidence: 99%